2016
DOI: 10.2147/dddt.s91374
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of monoclonal antibodies targeting interleukin-17 pathway for inflammatory arthritis: a meta-analysis of randomized controlled clinical trials

Abstract: T-helper 17 (Th17) pathway plays an important and distinct role in autoimmunity and inflammation. A growing body of evidence demonstrates that interleukin-17 (IL-17) is also synthesized in inflammatory arthritis tissues and exerts potent proinflammatory and joint-destructive activities. Clinical studies have been performed to evaluate the therapeutic efficacy of antibodies blocking the IL-17 signaling pathway in patients with rheumatoid arthritis (RA). In this study, we performed a meta-analysis to systematica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…However, adverse events of the treatment should be realized, such as impaired peripheral immune tolerance, reduction in natural killer (NK) cells, increased pulmonary embolism and hemorrhagic stroke . In addition, interleukin‐17 (IL‐17) has been demonstrated to play important roles in RA, and targeting IL‐17 gives potential therapy . It is notable that treatment on RA patients with monoclonal antibodies against IL‐17 may cause adverse effects, including diarrhea, leukemia, laryngeal abscess, interstitial lung disease and brachial plexopathy .…”
Section: Introductionmentioning
confidence: 99%
“…However, adverse events of the treatment should be realized, such as impaired peripheral immune tolerance, reduction in natural killer (NK) cells, increased pulmonary embolism and hemorrhagic stroke . In addition, interleukin‐17 (IL‐17) has been demonstrated to play important roles in RA, and targeting IL‐17 gives potential therapy . It is notable that treatment on RA patients with monoclonal antibodies against IL‐17 may cause adverse effects, including diarrhea, leukemia, laryngeal abscess, interstitial lung disease and brachial plexopathy .…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [16] reported that the number of Th17 cells in RA patients was significantly higher than that in the control group, and the amount of synovial fluid was related to the serum IL-17A level and the severity of joint damage. Blocking IL-17A and TNF-α has a synergistic effect on inhibiting IL-6 production and collagen degradation in RA synovial fluid and synovial fluid [17]. Therefore, Th17 cells can be used as a new target for the treatment of RA.…”
Section: Th17 Cells and Rheumatoid Arthritismentioning
confidence: 99%
“…Specifically, IL-17-blocking antibody significantly reduced ACR20 and ACR50. It also dramatically reduced DAS28, an index that measures tenderness and swelling severity of joints [Wei and Duan, 2016].…”
mentioning
confidence: 99%